2017
DOI: 10.1136/tsaco-2017-000084
|View full text |Cite
|
Sign up to set email alerts
|

Protecting study participants in emergency research: is community consultation before trial commencement enough?

Abstract: BackgroundThis article presents the results of a community consultation (CC) process completed in Toronto, Ontario, using a random digit dialling technique, on the attitudes and perceptions of the public toward the use of exception from informed consent when conducting emergency research involving the use of massive blood transfusions.MethodsIn 2012, our hospital conducted a CC, using a random digit dialling technique, to elicit the attitudes and perceptions of the public toward the use of an exemption from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Delayed consent was generally acceptable to respondents if the interventions offered direct benefit to the research participant, if the participant's condition was life-threatening and the work held the prospect of benefit for future patients, and if the protocol for delayed consent was approved by a human research ethics committee. Our findings on the acceptability of delayed consent for EC research are comparable to research done in other settings, such as Australia (62%) [33], Canada (76%) [34], and the United States (70%) [35]. A recent systematic review also showed comparable results in pediatric EC research (68%) [36].…”
Section: Discussionsupporting
confidence: 81%
“…Delayed consent was generally acceptable to respondents if the interventions offered direct benefit to the research participant, if the participant's condition was life-threatening and the work held the prospect of benefit for future patients, and if the protocol for delayed consent was approved by a human research ethics committee. Our findings on the acceptability of delayed consent for EC research are comparable to research done in other settings, such as Australia (62%) [33], Canada (76%) [34], and the United States (70%) [35]. A recent systematic review also showed comparable results in pediatric EC research (68%) [36].…”
Section: Discussionsupporting
confidence: 81%
“…Several trials have published survey data from 1 or more sites, but these studies capture only isolated snapshots of community attitudes regarding EFIC. [7][8][9][10][11][12][13][14][15][16][17][18] To our knowledge, the largest systematic review of EFIC survey data to date examined 9 trials with 9036 respondents but included only published data and did not quantitatively assess the demographic characteristics of those surveyed. 19 To comprehensively evaluate public attitudes regarding EFIC trials and avoid publication bias, we conducted a systematic review of all EFIC survey data submitted directly to the FDA since initiation of the EFIC pathway in November 1996 through October 2017.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited literature on community consultation surveys in EFIC trials. Several trials have published survey data from 1 or more sites, but these studies capture only isolated snapshots of community attitudes regarding EFIC . To our knowledge, the largest systematic review of EFIC survey data to date examined 9 trials with 9036 respondents but included only published data and did not quantitatively assess the demographic characteristics of those surveyed .…”
Section: Introductionmentioning
confidence: 99%
“…Two types of value for community consultation were frequently emphasized: 1) the ability to clarify impact of trial enrollment on potential enrollees and ways to refine the study and 2) the potential to promote trust, provide transparency, and demonstrate respect 5–13 . There were questions raised about the extent to which community consultation accomplishes these goals, especially identifying changes 14–19 . A key theme was the reiteration that community consultation is not intended to be a “consent” process or vote, although acceptance is relevant 6,9,20,21 .…”
Section: Resultsmentioning
confidence: 99%